Socio-Economic Implications of Abroad Mobility of Nepalese Students for Higher Education - Gautam, Govinda (Janapriya Journal of Interdisciplinary Studies, 2024)
Foreign mobility in higher education has been a persistent issue in almost every country especially in developing countries like Nepal for many years, resulting in a shortage of skilled and competent individuals within the country. This research investigates the socioeconomic implications of students’ mobility from Nepal to foreign countries. It aims to achieve two primary objectives: first, to identify the determinants driving students’ decisions to study abroad and secondly to analyze the socio-economic implications of this mobility on Nepal. A qualitative research approach is adopted, incorporating both primary and secondary data sources. Six Nepali students studying in various foreign countries and six parents whose children are currently residing abroad are interviewed using a semi-structured format of questions to explore the determinants and motivations behind international education decisions. Additionally, a systematic review of related literature is conducted, drawing from academic databases, reputable journals, and official reports to provide a comprehensive analysis. The qualitative data are thematically analyzed, complemented by findings from the literature review. Ethical considerations have been adhered to throughout the study. The research has aimed to shed light on the impact of foreign mobility on students and their families in Nepal and contribute valuable insights to the field of international education. Understanding the factors that influence students mobility and the resulting outcomes is likely to be crucial for policymakers, educational institutions, and students themselves